ANALYTICS DRIVEN DATA MODEL IN DIGITAL SERVICES - Keat, Ng Wai (Journal of Technology Management and Business, 2018)
Data models are generally applied to construct consolidated abstraction of various rich and different domains of data. In this paper, we focus on the digital services domain in particularly customer related data model and its structure in helping to shape the analytics capabilities. The traditional Entity Relationship Diagram (ERD) is used as the cornerstone of the strategy and further elaboration is made through abstraction to encompass areas in the digital services. A data model is developed to cover both static aspects (customers’ profile) and dynamic aspects (customers’ behaviour). The foundation of the customer aspect is constructed in classes that represent different types of customer touch points represented as digital footprint which analogize physical activities. The customer dynamic aspects of digital service are modeled with a group of classes where priority is embodied in different associations involving creation and termination of the identified interaction. The suggested data model can be deployed in development of frameworks for customer related applications and enhancement of analytics capabilities. Keywords: Data model, Analytics, Digital services